Культиватор для выращивания хлореллы в искусственных условиях; Архитекторы будущего - Алексеев М. А.; Иванова С. С.; Коршунов К. О.; Трофимчук О. А. Оксана Анатольевна; Шевченко И. Г. (2014, 2014)
Заглавие с титульного экрана